Surveillance of leptospiral reservoirs in synanthropic rodents using loop-mediated isothermal amplification - Hamer, Micaela; Saraullo, Vanina Rosa; Muschetto, Emiliano; Esteban, Micaela; Tripodi, Mariel Alejandra; Sanchez, Maria Cristina; Hancke, Diego; Suárez, Olga Virginia; Brihuega, Bibiana Felicitas; Martinez, Mara Leila (Elsevier, 2025)
Leptospirosis, a zoonotic disease caused by pathogenic Leptospira spp., represents a major public health concern due to its impact on both rural and urban populations. Rodents, particularly Rattus norvegicus, Rattus rattus, and Mus musculus, are key reservoirs, excreting leptospires in their urine and contributing to environmental contamination. In this study, we evaluated the efficacy of loop-mediated isothermal amplification (LAMP), a molecular diagnostic tool, for detecting leptospiral DNA in kidney samples from captured rodents. LAMP results were compared with the standard lipL32 PCR assay. Leptospiral DNA was detected in 9.0 % (14/156) of samples, with 5.8 % positive by both LAMP and lipL32 PCR and 3.2 % positive by LAMP alone. No samples were positive by PCR and negative by LAMP. Cohen's Kappa index (0.77) indicated substantial agreement between the two methods. The higher sensitivity of LAMP, its ability to detect both pathogenic and intermediate leptospiral strains, and its cost-effectiveness make it a valuable tool for low-resource settings. However, the technique’s inability to differentiate between Leptospira species highlights the need for complementary methods for epidemiological studies. These findings contribute to the understanding of rodent leptospirosis reservoirs and offer practical diagnostic solutions for veterinary and public health surveillance.